Transformative agroecology learning in Europe: building consciousness, skills and collective capacity for food sovereignty - Anderson, Colin R.; Maughan, Chris; Pimbert, Michel P. (Agriculture and Human Values, 2018)
Agroecology has been proposed as a key building block for food sovereignty. This article examines the meaning, practices and potentials of ‘transformative agroecology learning’ as a collective strategy for food system transformation. Our study is based on our qualitative and action research with the European Coordination of Via Campesina to develop the European Agroecology Knowledge Exchange Network (EAKEN). This network is linked to the global network of La Via Campesina and builds on the strong experiences and traditions of popular education in Latin American peasant movements. Rather than focusing on agroecology education as a process of individual learning, we analyse how a transformative agroecology education can be strengthened as a critical repertoire of action used by social movements to advance food sovereignty. Our analysis contributes a new theory of transformative agroecology learning based on four key characteristics or qualities: horizontalism; diálogo de saberes (wisdom dialogues); combining practical and political knowledge; and building social movement networks. While these different elements of transformative agroecology learning were present across EAKEN, they were unevenly developed and, in many cases, not systematized. The framework can help to strategically and reflexively systematize and strengthen a transformative agroecology learning approach as a key building block for food sovereignty.
Keywords: Agroecology; Europe; Food sovereignty; Learning; Pedagogy; Popular education; Sustainable agriculture